STRATEGI KOMUNIKASI PEMBERDAYAAN MASYARAKAT PADA PENGEMBANGAN DESA SIAGA AKTIF MANDIRI (STUDI KASUS DI DESA BRINGIN BENDO KECAMATAN TAMAN KABUPATEN SIDOARJO - Ratna Ayu Permananingtyas, 071514853027 (2017)
Desa Siaga Aktif (Active Alert Village) is a national campaign program aim to create village communities that can recognized and able to address their ownhealth problems independently. The independence can be occured by the development of activities and program run by the villagers themselves. There only five villages in Sidoarjo regency reach the independent stage, one of them is BringinBendo. Effective communication by the community empowerment cadres contributes more in the success of active alert village conducted in Bringin Bendo.This research proposed to give a critical and comprehensive description of communication strategy for community development in BringinBendo Village, Taman SidoarjoSubdistrict.Health Promotion and Communication Strategy for Community Development designed by United Nation’s Children Fund (UNICEF) can be used to explain the program implementasion in Bringin Bendo. The research used qualitative approach, descriptive type with case study method. The informants consisted of health cadres, midwives, village apparatus, and the community. Data are collected through in-depth interviews, observations, and relevant documentation sources. The community development strategy in BringinBendo Village focuses on participatory communications of three key groups, namely advocacy to village leaders and community leaders, social mobilization to community social organizations, community groups and the private sector, and communication for behavioral change to specific target individuals and groups. Communication strategies are carried out in a formal way through meetings, as well as informally with persuasive approaches, face-to-face communication, participatory dialogue, in an informal and familial atmosphere.